Evaluation of Weak Form of Market Efficiency Theory Based on Daily Data for Five Companies from Nifty - Parulekar, Pushkar Dilip (SFIMAR Research Review, 2018)
Since the introduction of "Efficient Market Hypothesis" (EMH) or Market efficiency theory by Professor Eugene Fama there has been a lot of research supporting and contradicting the theory. There are three variants to the theory "weak", "semi-strong", and "strong" form. The weak form of the EMH claims that prices of traded assets (e.g., stocks, bonds or commodity) already reflect all the past price and volume information about the asset. The semi-strong form of the EMH claims that prices reflect all publicly available information including past price and volume data and that prices instantly change to reflect new public information. The strong form of the EMH additionally claims that prices instantly retlect even hidden "insider" information. The research paper tries to review "weak" form of market efficiency for selected five companies. Five different companies from tive different sectors are being considered viz. Infosys Limited, Hindustan Unilever Limited, Larsen and Toubro Limited, Mahindra and Mahindra Limited and Sun Pharmaceutical Industries Limited. These companies represent various sectors in the economy viz. Information Technology (IT), Fast Moving Consumer Goods (FMCG), Capital goods (CG), Automobiles (Auto) and Pharmaceuticals (Pharma). To test the "weak" form of market efficiency daily data from 1st April 2004 to 31st March 2016 would be considered. Statistical tests such as "Runs Test" and "Autocorrelations" would be used to infer from the data